Aerodynamic modelling of flapping insect: a review - Abdul Hamid, Mohd Faisal; Filippone, Antonio (SAGE Publications, 2022)
A review of the aerodynamic modelling of insect flight is presented. This paper consists of two sections covering various aspects related to the development of flapping wing and research on the aerodynamic modelling of insect flight. First, we provide an overview of the nature of the flyers, including current issues and challenges related to the evolution of nature-inspired design. The second section discusses some of the techniques required to develop aerodynamic models, seeks to address issues and to identify appropriate aerodynamic modelling methods for the development of insect flight models. Experimental models of flapping wing insect are discussed, followed by numerical models. Finally, we highlight the development of prototypes in insect flight, on the design, sizing and classification of the flying insect prototypes.